Physical and Mathematical Modeling of non Transferred Plasma Torches - Favalli,R. C. (1998)
The main objective of this work is to obtain temperature and velocity profiles of the plasma jet, including the electric arc region, generated by non transferred plasma torches. The profiles are obtained from a numerical solution of the conservation equations wich were used to describe the plasma flow. This modelling approach will help the development and optimization of plasma torches, saving time and reducing costs of an alternative empirical development; it could also give some insight on the phenomena occuring inside the torch. Fluid mechanics models for laminar and turbulent flows were adopted to simulate the plasma inside and outside the torch. Patankar's control volume method was chosen to solve the resulting coupled differential equations. The method is very stable and requires less computational time than higher order methods, although it can be less accurate for some applications. A computer code was developed to simulate the jet flow of a plasma torch. The results obtained from this program compared very well with published ones, corroborating the assumptionsn of the present model and the numerical method. Temperature and velocity profiles for a plasma torch with dimentions and operating conditions similar to the ones used in indusrtial applications of spraying were generated and analyzed. The plasma torch simulated had an eletric arc of 100A, plasma gas flow rate of 20 l / min, cross section of 5.2 mm and anode length of 13mm.